Lexical Transformation And Its Types - Kasimova Nafisa Farhodovna; Safarova Maftuna (Genius Publishing Group, 2025)
This study explores lexical transformations in translation, focusing on concretization, generalization, addition (explicitation), and omission. These procedures are essential for achieving semantic equivalence, cultural adequacy, and stylistic naturalness in the target text. Concretization increases precision by replacing general terms with specific ones, while generalization simplifies overly specific expressions for clarity. The analysis of Gʻafur Gʻulom’s Shum bola (“Naughty Boy”) illustrates how these strategies enable translators to convey meaning accurately and naturally. The findings highlight that lexical transformations are dynamic, context-sensitive strategies rather than mechanical substitutions, emphasizing the creative and interpretive nature of translation.
Keywords: Lexical transformation; Concretization; Generalization; Translation strategies